2016
DOI: 10.1080/09540105.2016.1202211
|View full text |Cite
|
Sign up to set email alerts
|

Development of a specific monoclonal antibody assay and a rapid testing strip for the detection of apramycin residues in food samples

Abstract: A specific monoclonal antibody (MAb) against apramycin (AP) was produced and used to develop an indirect competitive enzymelinked immunosorbent assay (idcELISA) and a rapid testing strip for the detection of AP residues in foods. MAb exhibited negligible cross-reactivity with other aminoglycosides. Under optimized conditions in 0.01 M PBS, the half maximum inhibitory concentration (IC 50) of MAb was 0.41 ng/ml with a limit of detection (LOD) of 0.15 ng/ml. The ELISA results were obtained within 90 min. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…The strip test procedure and principle used in this study are a slight modification of that reported in earlier studies (Isanga, Tochi, et al, 2017;Luo et al, 2014). Briefly, 50 μL of the sample was added to the conjugate layer containing colloidal gold-labeled antibodies.…”
Section: Immunochromatographic Test Strip Procedures and Principlementioning
confidence: 99%
See 4 more Smart Citations
“…The strip test procedure and principle used in this study are a slight modification of that reported in earlier studies (Isanga, Tochi, et al, 2017;Luo et al, 2014). Briefly, 50 μL of the sample was added to the conjugate layer containing colloidal gold-labeled antibodies.…”
Section: Immunochromatographic Test Strip Procedures and Principlementioning
confidence: 99%
“…Amikacin is a small molecule lacking immunogenicity so in order to make it immunogenic, it needs to be conjugated to a larger carrier protein or carbohydrate Isanga, Tochi, et al, 2017;Xu et al, 2014). This conjugation can be made possible via one of the four amino or eight hydroxyl functional groups present in the amikacin chemical structure as shown in Figure 2(a).…”
Section: Synthesis Of Immunogens and Coating Antigensmentioning
confidence: 99%
See 3 more Smart Citations